THE ISSUE OF THE COMPRESSIVE STRENGTH OF FINE-GRAINED REINFORCED CONCRETE - Kseniya L. Domnina (Acta Tecnología, 2017)
To obtain high-quality concrete constructions it is not enough to execute it only in concrete of high class. One of the effective ways to improve the reliability and durability of concrete is its reinforcing by various kinds of fibers. The article presents the researching results of the influence of brands of portland cement and disperse reinforcing by polyethylene terephthalate fibers (PET-fiber) on concrete durability. Standard compression tests of the cubical prototypes of fine-grained sand concrete made of two brands of portland cement – PC400 and PC500 with different percentage of PET-fibers have been conducted. The optimum content of PET-fibe, wherein there is a maximum increase of durability of fine-grained fiber-reinforced concrete, has been set.